This House of Noble Deeds : the Mount Sinai Hospital, 1852-2002. - Aufses, Arthur H. (NYU Press, 2002)
On January 15, 1852, nine men representing various Hebrew charitable organizations came together to establish the Jews' Hospital in New York with a vision of offering free medical care to the indigent Hebrews in the City who were unable to provide for themselves during their illness. This was the beginning of The Mount Sinai Hospital. Now, a century and a half later, This House of Noble Deeds celebrates the scientific and medical achievements of The Mount Sinai Hospital. From its original 45-bed building, the Mount Sinai Medical Center has developed into a state-of-the-art facility comprising.